A study of supporting programs for small and medium enterprises: a first stage going to "Lean" - Real, R.; Pralus, M.; Pillet, M.; Guizzi, L. (2007 IEEE International Conference on Industrial Engineering and Engineering Management, 2007)
Nowadays, firms should adopt new production management systems to be competitive. Toyota production system (TPS) and Lean production are attractive systems. They promise good results to firms applying their concepts (mainly based on waste elimination and continuous improvement). Although Lean and TPS seem to be easy to apply, the field study we present in this paper reveals that they are not easy to maintain. In this paper, we present the main results of our survey and propose primary solutions. We interviewed nine consultants that supported more than sixty firms in Haute Savoie (France). The major conclusions of this survey can be split in indisputable benefits - such as a new method of work, the implication of the manager as a preliminary condition to the Lean and the successful implementation of the tools of Lean - and persistent failings like an unsuited. That's why we propose research tracks focused on standardization and contributing management.